SOCIOECONOMIC DISPARITIES IN EDUCATIONAL OUTCOMES ARISING FROM THE IMPLEMENTATION OF TECHNOLOGY-ENABLED LEARNING IN EARLY CHILDHOOD EDUCATION IN INDONESIA - Al-Amin; Ika Rahayu Satyaninrum; Cut Ita Erliana; Dahlan Abdullah; Mohd Syahrin (International Journal of Teaching and Learning, 2023)
The integration of technology in early childhood education has garnered significant attention worldwide. In 2021, Indonesia embarked on an ambitious journey to incorporate technology-enabled learning into its educational framework. This study retrospectively examines the socioeconomic disparities that emerged from this endeavor. Through extensive data analysis and assessments, it was observed that the introduction of technology in early childhood education had a mixed impact on the educational outcomes of children from various socioeconomic backgrounds. While children from affluent families exhibited enhanced digital literacy and cognitive development, those from economically disadvantaged households encountered disparities in access to technology and resources. The digital divide became more pronounced, leading to disparities in academic achievement. Furthermore, it was found that educators and policymakers encountered significant challenges in adapting the curriculum to address these disparities. The study also highlights the importance of addressing issues related to infrastructure and equity in technology access in early childhood education, ensuring that all children have an equal opportunity to thrive. These findings emphasize the necessity for a more inclusive and equitable approach to integrating technology in early childhood education, aiming to bridge the socioeconomic gaps and provide a level playing field for all children, thereby fostering a more equitable and promising educational landscape in Indonesia.